Parahesione dudahamra sp. nov., an eye-catching symbiotic worm from the Red Sea, with complementary description and notes on Leocrates giardi Gravier, 1900 (Annelida: Phyllodocida: Hesionidae) - Syomin, Vitaly; Anker, Arthur; Kolbasova, Glafira; Carvalho, Susana (Zootaxa, 2025)
A new, brightly red-coloured, symbiotic hesionid worm, Parahesione dudahamra sp. nov., is described based on the holotype and single specimen collected in the shore waters of the King Abdullah University of Science and Technology, Thuwal, Red Sea coast of Saudi Arabia. The new species is characterized by simple lateral antennae without distinct ceratophores, longest dorsal cirri reaching chaetiger 12, and longest ventral cirri reaching only chaetiger 4. The holotype was extracted from a burrow of an unknown host in very shallow water, close to mangrove roots. The diversified burrowing fauna of the type locality, including the possible infaunal hosts of P. dudahamra sp. nov., is briefly discussed. In addition, a full description and ecological notes are provided for another hesionid worm, Leocrates giardi Gravier, 1900, of which several specimens were extracted from burrows at the type locality of P. dudahamra sp. nov.